Modelo logístico de distribución, entrega de productos e integración de información en la ferretería Bonilla del cantón La Maná - Rubio Enriquez, Mery Fernanda (2019)
This research project is focused on the proposal of a logistics system for distribution, delivery of products and integration of information in the "Bonilla" hardware store, located in the city of La Maná, which presents the dissatisfaction of its customers due to Excessive delay at the time of dispatch of orders, for this and in compliance with the objectives set is an analysis of the processes where it could be determined as the main factor that influences the wrong Layout of the distribution of the plant showing it, To this is added as an alternative the proposal of a new Layout of distribution, this entails to implement technological material that integrates and improves the flow of information between the adjacent areas that will allow to improve the delivery times and to manage only the necessary activities that add value, maintaining the optimum number of units and decreasing the risk of lack of merchandise of the best products that the company has. Keywords: Company - Distribution - Products - Integration of information - TICs.